(3ebOeI aj GdbjGS GdGbJUGOj (B/s - (3cGXe, GehQj gGOjs ((3YeGf(B: s (3OGQ GdRgQGf(B, s, 2009)
(3GdfehPL GdNWj GdHSjW h GdfehPL GdNWj GdYGe , eTcdI YOe JLGfS GdJHGjf h eTcdI GdEQJHGW GdPGJj , eTcdI GdJYOO GdNWj , GdbjhO GdeJWGHbI h efXheI GdeYGOdGJ GdBfjI eY hLhO CSFdI YGeI eMdhdIs
(3LOGhd GMUGFjI U(B.345(3, eUGOQ U(B.355s
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdGbJUGOs; (3GdEbJUGO GdbjGSjs